HUBUNGAN FAMILY EMPOWERMENT DENGAN KUALITAS HIDUP LANSIA YANG HIPERTENSI DI DESA BOJONG KECAMATAN TENJO KABUPATEN BOGOR - Haryanto, Sri; Hasanah, Uswatun; Anggraeni, Reska Widya; Firmansyah, Miftah Parid; Rahmi, Junaida; Darmayanti, Desy (Edu Dharma Journal :Jurnal penelitian dan pengabdian masyarakat, 2025)
ASBTRACT According to WHO data in 2019, the elderly population in the world was estimated to be 7.2% or around 142 million people, and this figure is expected to increase to 20.3%. Family empowerment is an effort used to create or improve the quality of life of families, both individually and collectively, in solving various issues related to efforts to enhance the quality of life, independence, and welfare of the community. The purpose of this research is to determine the relationship between family empowerment and the quality of life of elderly individuals with hypertension in Bojong Village, Tenjo District, Bogor Regency. The research method is a quantitative study with a Cross Sectional design. Sampling was conducted using the Probability Sampling technique with the Simple Random Sampling method, involving 54 respondents. Data analysis used the Chi Square test with a significance level of p